Study Program Performance Report (LKPS) Information System in the Web-Based Information Systems Study Program Using the RAD Method - Ramadhani, Isma; Zakir, Ahmad; Lubis, Fachrul Rozi (Cattleya Darmaya Fortuna, 2024)
In the process of compiling the Study Program Performance Report (LKPS) in the information systems study program of the Faculty of Engineering and Computer, Universitas Harapan Medan, it is still done manually, namely by using Microsoft Office Excel, so it takes a long time to collect data and compile the report and there is no media to collect evidence that supports the preparation of the Study Program Performance Report (LKPS). Therefore, a system was built as a medium to collect supporting evidence for the preparation of the Study Program Performance Report (LKPS) and to store Study Program Performance Report (LKPS) data in the information systems study program. In designing the construction of this website-based LKPS information system, a system development method will be used, namely the Rapid Application Development (RAD) Method. This system is built using the PHP programming language and MySQl as its database with the data modeling used is UML. Based on the black box testing of the LKPS Information System, all existing buttons can run according to their functions. In the end result, it was obtained that the system can run as expected and make it easier to manage data for compiling LKPS.